2018
DOI: 10.1038/s41467-018-02886-w
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide resolution mapping of influenza A virus nucleoprotein-RNA interactions reveals RNA features required for replication

Abstract: Influenza A virus nucleoprotein (NP) association with viral RNA (vRNA) is essential for packaging, but the pattern of NP binding to vRNA is unclear. Here we applied photoactivatable ribonucleoside enhanced cross-linking and immunoprecipitation (PAR-CLIP) to assess the native-state of NP–vRNA interactions in infected human cells. NP binds short fragments of RNA (~12 nucleotides) non-uniformly and without apparent sequence specificity. Moreover, NP binding is reduced at specific locations within the viral genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 40 publications
(56 reference statements)
8
81
1
Order By: Relevance
“…The vRNP is responsible for transcription and replication of constituent vRNAs and the incorporation of vRNAs into progeny virions. Recent studies show that NPs, in the context of vRNPs, bind to vRNAs nonuniformly without sequence specificity . Importantly, next‐generation sequencing analyses have demonstrated that some regions of the vRNAs, in the context of vRNPs, are free of NPs and able to form secondary or tertiary structures on the surface of the rod‐shaped vRNPs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vRNP is responsible for transcription and replication of constituent vRNAs and the incorporation of vRNAs into progeny virions. Recent studies show that NPs, in the context of vRNPs, bind to vRNAs nonuniformly without sequence specificity . Importantly, next‐generation sequencing analyses have demonstrated that some regions of the vRNAs, in the context of vRNPs, are free of NPs and able to form secondary or tertiary structures on the surface of the rod‐shaped vRNPs …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that NPs, in the context of vRNPs, bind to vRNAs nonuniformly without sequence specificity. 1,2 Importantly, next-generation sequencing analyses have demonstrated that some regions of the vRNAs, in the context of vRNPs, are free of NPs and able to form secondary or tertiary structures on the surface of the rod-shaped vRNPs. 3 It has been demonstrated that progeny virions selectively package a single copy of each of the eight vRNAs.…”
mentioning
confidence: 99%
“…A revised influenza virus genome architecture has recently been proposed, which suggests that NP binds vRNA in a non-uniform and non-random manner [18, 21], but how this apparent NP specificity is achieved remained unanswered. It was thus unclear whether nucleotide changes in vRNA would alter the NP binding profile, or whether the NP binding profile would remain static due to an as-yet unidentified mechanism that would maintain NP binding at the original positions in the vRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of HITS-CLIP is that, unlike other versions of the CLIP methodology, such as iCLIP or eCLIP [19], it uncovers the entire footprint of vRNA protected by NP rather than focusing on the NP-crosslinked sites on vRNA. Another study utilizing PAR-CLIP (photoactivatable ribonucleoside-enhanced crosslinking and immunoprecipitation) [20], a technically related version of HITS-CLIP that can also identify NP binding sites with nucleotide resolution, reached the same conclusion that NP binding is not pervasive throughout the segments inside infected host cells [21].…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis and the work of others showed that the segment ends are highly conserved for all 8 segments [16][17][18][19][20][21] . The segment ends are potentially attractive regions for targeting with Cas13d because of the potential to inhibit a broad range of IAV strains and because of the previous evidence that interfering with the packaging of one segment encoded on the segment ends can decrease the packaging efficiency of other segments and overall virion packaging 18,[22][23][24][25] . Using sequence representation from ~140 different strains of influenza, we designed crRNAs that could be robust across as many different IAV strains as possible.…”
Section: Crispr Pac-man Is Able To Inhibit Iav Infection In Human Lunmentioning
confidence: 99%